Building Youth Resiliency and Community Vitality Within Montreal’s English Language Population : The YES Experience with Youth Seeking to Improve their Work Situation - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2013)
In response to an increase in the number of clients’ experiencing mental health challenges in the course of their job search YES (through CHSSN) has commissioned this report to establish an evidence-based profile of the youth that they serve. At the present time, YES uses limited resources to offer additional support through a focus group that is designed for clients who are experiencing symptoms such as decreased motivation, anxiety, social isolation and diminished confidence in dealing with the transition process.
Keywords: Official Language Minority Community (OLMC)

Brief Regarding the General Consultation and Public Hearings on Bill 14 : An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Voice of English-speaking Quebec (VEQ) (2013)
The purpose of this brief is to highlight the potential impacts that the proposed Bill 14 could have on the minority English-speaking community of the Greater Quebec City region. As the preeminent interest group representing English-speakers in the Quebec City region, VEQ has carefully analyzed all the modifications included in the proposed Bill 14 and has consulted its membership, community and many of its key partners in order to present this comprehensive evaluation of the impacts that Bill 14 could have on our community. It is our opinion that Bill 14, if adopted in its present form, will have several negative consequences on the vitality of our community and on the capacity of English speakers to continue to be contributing citizens of our region. In addition, we sincerely believe that Bill 14 will also have a real negative impact on the capacity of our entire region to attract and retain English-speaking immigrants and migrants which will directly affect the economic prosperity of the Quebec City region.
Keywords: Official Language Minority Community (OLMC)